Maternal exposure to fine particulate matter from a coal mine fire and birth outcomes in Victoria, Australia. (June 2019) - Melody, Shannon M.; Ford, Jane; Wills, Karen; Venn, Alison; Johnston, Fay H.
Abstract: Introduction: The Hazelwood coal mine fire was an unprecedented event in Australian history that resulted in the surrounding towns in regional Victoria being covered in plumes of smoke and ash for six weeks in 2014. Evidence concerning adverse reproductive impacts associated with maternal exposure to ambient air pollution is expanding. Gaps remain regarding the relative impact of acute changes in outdoor air quality lasting days to months, such as that resulting from coal mine fires. Methods: Routinely collected perinatal data was used to define a complete cohort of singleton babies born within the affected region. Maternal average, and peak, fine particulate matter (PM2.5 ) was assigned to residential address at time of delivery using a chemical transport model. Maternal, infant, meteorological and temporal variables were adjusted for in final linear and log-binomial regression models. Results: There were a total of 3591 singleton livebirths during the study period; 763 of which were in utero during the coal mine fire. Average PM2.5 exposure was 4.4 μg/m 3 (median 1.9; IQR 2.1 μg/m 3 ) and peak was 45.0 μg/m 3 (median 30.4; IQR 35.1 μg/m 3 ). There was no association between coal mine fire-attributable PM2.5 and fetal growth or gestational maturity outcomes. However, there was weak evidence that gestational diabetes mellitus was an effect modifier in the relationship between maternal PM2.5 exposure and birth weight. Babies born to exposed gestational diabetic mothers were 97 g heavier per 10 μg/m 3 increase in average PM2.5 exposure (95%CI 74, 120 g). No association was observed among mothers without gestational diabetes. Conclusion: Maternal exposure to fine particulate matter resulting from the 2014 Hazelwood coal mine fire did not appear to adversely effect fetal maturity. However, there was weak evidence of a trophic response among babies born to exposed mothers with gestational diabetes, a possible susceptibility that requires further exploration. Highlights: The 2014 Hazelwood coal mine fire was a severe smoke event in regional Australia. This study found no association between PM2.5 exposure and fetal growth or maturity. Gestational diabetes was an effect modifier between PM2.5 exposure and birth weight. Babies of gestational diabetes mothers were 97 g heavier per 10 μg/m 3 increase in PM2.5 . Women with gestational diabetes may be particularly vulnerable to smoke events.